1997
DOI: 10.4315/0362-028x-60.7.811
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of Listeria Ribotypes Recovered from Dairy Cattle, Silage, and Dairy Processing Environments

Abstract: Listeria strains isolated over the past 10 years from farms and dairy processing environments were subjected to strain-specific ribotyping using the automated Riboprinter microbial characterization system, alpha version (E. I. du Pont de Nemours & Co., Inc.). A total of 388 Listeria isolates from 20 different dairy processing facilities were examined along with 44 silage, 14 raw milk bulk tank, and 29 dairy cattle (26 udder quarter milk, 1 brain, 1 liver, and 1 aborted fetus) isolates. These 475 isolates i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(29 citation statements)
references
References 0 publications
1
28
0
Order By: Relevance
“…Rather, our data indicate that the L. monocytogenes subtype populations found on farms overlap with those responsible for human listeriosis cases. While most raw foods originating from ruminant farms undergo heat treatments that effectively inactivate L. monocytogenes, farms may serve as a source of L. monocytogenes strains that are inadvertently introduced into food-processing environments and subsequently transferred onto foods through postprocessing contamination (1,45). For example, subtype data for a total of 475 Listeria isolates from different dairy processing facilities and farms showed that 8 L. monocytogenes and 12 Listeria species ribotypes were found in both dairy-processing and farm environments, supporting the potential of on-farm sources to contribute to processing plant contamination (1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rather, our data indicate that the L. monocytogenes subtype populations found on farms overlap with those responsible for human listeriosis cases. While most raw foods originating from ruminant farms undergo heat treatments that effectively inactivate L. monocytogenes, farms may serve as a source of L. monocytogenes strains that are inadvertently introduced into food-processing environments and subsequently transferred onto foods through postprocessing contamination (1,45). For example, subtype data for a total of 475 Listeria isolates from different dairy processing facilities and farms showed that 8 L. monocytogenes and 12 Listeria species ribotypes were found in both dairy-processing and farm environments, supporting the potential of on-farm sources to contribute to processing plant contamination (1).…”
Section: Discussionmentioning
confidence: 99%
“…While farms may serve as direct or indirect sources of L. monocytogenes strains that are introduced into the human food chain (1,45), they also represent ecosystems that could facilitate the emergence of new and more virulent L. monocytogenes subtypes in a high-transmission-frequency environment. While cattle have been identified as potentially important reservoirs for Escherichia coli O157:H7 (29) and certain Salmonella serotypes (9,43), their role as a reservoir for L. monocytogenes is likely to be different and more complex, since, in contrast with Salmonella and E. coli O157:H7 infections, raw animal-derived food products are rarely a direct source of human listeriosis.…”
Section: Vol 70 2004 Ecology and Transmission Of L Monocytogenes 4465mentioning
confidence: 99%
“…Some specific subtypes of L. monocytogenes can also persist for extended periods in many different food processing environments , including dairy food processing plants (Vazquez-Villanueva et al, 2010;Latorre et al, 2011). In the dairy plant, Listeria can persist in a variety of sites, although it is most frequently found in moist environments or areas with condensed or standing water or milk, including drains, floors, coolers, conveyors and case washing areas (Arimi et al, 1997;Ho et al, 2007b;Fox et al, 2009).…”
Section: Processing Environmentmentioning
confidence: 99%
“…The processing environ-ment is the main origin of contamination of processed food with Listeria. Contamination of the processing environment results from on-farm Listeria contamination from silage, dairy cattle and raw milk (Arimi et al, 1997). Processors must specifically enforce restrictions and procedures that prevent cross-contamination between the dairy farm environment and the processing environment (Ho et al, 2007b) as well as between raw and processed food.…”
Section: Ecology Of Listeria Monocytogenes and Molecular Subtyping Mementioning
confidence: 99%
“…It has been demonstrated that the discriminatory power of this technique can considerably increase by using multiple ribopatterns to determine the overall ribotype of isolates [194]. Ribotyping has been widely used to characterise milk-and dairy-borne isolates of L. monocytogenes [195][196][197][198][199][200], S. aureus [201,202], E. coli O157:H7 [203,204], Salmonella spp. [205] and Campylobacter spp.…”
Section: Typingmentioning
confidence: 99%